2010
DOI: 10.1017/s0007114510004058
|View full text |Cite
|
Sign up to set email alerts
|

The fat and protein fractions of freshwater clam (Corbicula fluminea) extract reduce serum cholesterol and enhance bile acid biosynthesis and sterol excretion in hypercholesterolaemic rats fed a high-cholesterol diet

Abstract: We investigated whether the fat and protein fractions of freshwater clam (Corbicula fluminea) extract (FCE) could ameliorate hypercholesterolaemia in rats fed a high-cholesterol diet. We also explored the mechanism and the components that exert the hypocholesterolaemic effect of FCE. The doses of the fat and protein fractions were equivalent to those in 30 % FCE. The fat and protein fractions of FCE, two major components of FCE, significantly reduced the serum and hepatic cholesterol levels. The fat fraction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
3
32
1
Order By: Relevance
“…11,[14][15][16][17][18] Briefly, freshwater clams were steamed until their shells opened, and then the edible portions were removed. Edible portions were minced, extracted with boiling water, and passed through an 80-mesh filter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[14][15][16][17][18] Briefly, freshwater clams were steamed until their shells opened, and then the edible portions were removed. Edible portions were minced, extracted with boiling water, and passed through an 80-mesh filter.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that freshwater clam extract (FCE) protects against liver injury, [11][12][13] ameliorates hypercholesterolemia [14][15][16][17] and fatty liver disease, 11,15) and accelerates ethanol metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Buhman et al also demonstrated that feeding psyllium to rats enhanced the level of hepatic cholesterol 7α-hydroxylase mRNA as well as fecal bile acid and total steroid excretions [47]. Chijimatsu et al speculated that the hypocholesterolaemic effects of freshwater clam (Corbicula fluminea) extract might be due to increased fecal neutral sterol, bile acid excretion and hepatic cholesterol 7a-hydroxylase gene expression [4]. Another group has also demonstrated beneficial effects of the fermented adzuki bean paste on serum cholesterol in rats.…”
Section: Am Effects On the Levels Of Serum Total Cholesterol And Fecamentioning
confidence: 99%
“…As intake of meat increases, blood cholesterol increases due to excess of cholesterol intake [3]. Chijimatsu et al fed high cholesterol diet to rats leading to the increase in blood cholesterol in these rats [4].…”
Section: Introductionmentioning
confidence: 99%